2013
DOI: 10.1248/bpb.b12-00437
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive Effects of Oral Administration of Heat-Killed <i>Lactobacillus acidophilus</i> on T Helper-17 Immune Responses in a Bovine β-Lactoglobulin-Sensitized Mice Model

Abstract: The present study was planned to explore the effect of Lactobacillus (L.) acidophilus on the T helper-17 (Th17) immune response in a mouse model of β-lactoglobulin (β-lg) allergy. Bovine β-lg sensitised BALB/c mice were orally administered with different doses of heat-killed L. acidophilus (low, 5×10 7 colony forming unit (CFU); medium, 5×10 8 CFU; high, 5×10 9 CFU) in 200 µL of phosphate buffered saline (PBS) three times a week, starting from 1 week before β-lg sensitisation for 4 weeks. After the allergen ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…In an allergy murine model, L. acidophilus attenuated IL-6 and IL-17 serum levels and downregulated the expression of IL-17A and retinoic acid-related orphan receptor gamma t in the spleen. 29 Recently, oral administration of L. acidophilus was found to inhibit the expression of IL-17, TNF-a, and IL-23, as well as STAT3 and phosphorylated STAT3 in colon tissue in a DSS-induced colitis model. 20 With respect to Treg cells, treatment with L. acidophilus augmented the expansion of Treg cells in intestinal intraepithelial and lamina propria lymphocytes in a 2,4,6-trinitrobenzene sulfonic acid-induced colitis model.…”
Section: Discussionmentioning
confidence: 99%
“…In an allergy murine model, L. acidophilus attenuated IL-6 and IL-17 serum levels and downregulated the expression of IL-17A and retinoic acid-related orphan receptor gamma t in the spleen. 29 Recently, oral administration of L. acidophilus was found to inhibit the expression of IL-17, TNF-a, and IL-23, as well as STAT3 and phosphorylated STAT3 in colon tissue in a DSS-induced colitis model. 20 With respect to Treg cells, treatment with L. acidophilus augmented the expansion of Treg cells in intestinal intraepithelial and lamina propria lymphocytes in a 2,4,6-trinitrobenzene sulfonic acid-induced colitis model.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that oral administration of L. acidophilus KLDS 1.0738 had protective effects on β‐Lg–induced hypersensitivity, characterized by inhibition of IgE production, regulation of the imbalance in Th cell subsets, and induction of oral tolerance . Recent reports in animal models and in clinical trials confirmed that the immunoinhibitory effects of probiotics were dependent on improving the gut microflora composition and SCFA metabolism .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicated that application of lactobacilli could attenuate airway hyperreactivity by induction of Tregs in a mouse model of asthma (Jan et al 2012;Karimi et al 2009). We also showed Lactobacillus acidophilus strain KLDS 1.0738 had the ability to suppress the β-lg allergic symptoms and Th17 cytokine production (Li et al 2013). Moreover, some studies focused on the effect of probiotics on activating the cytokine-mediated STAT pathways to regulate the immune responses.…”
Section: Introductionmentioning
confidence: 83%
“…Subsequently, we observed that oral administration of L. acidophilus KLDS 1.0738 suppressed β-lg-induced inflammatory, including alleviating eosinophil inflammatory influx and the severe histologic features in the colons and lungs of the sensitized mice. It was previously shown that L. acidophilus treatment could increase the Treg-related cytokines and transcription factor production (IL-10, TGF-β1, Foxp3) but suppress the Th17-type levels (IL-17A, RORγt) (Li et al 2013). In this study, addition of L. acidophilus to β-lg-immunized mice could significantly upregulate the number of Treg cells and downregulate the number of Th17 cells compared with the allergy group (P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation